Rupture Resistance: An Archaeology of Pedophilia Crisis Communication. Issue 2 (15th March 2017) - Langett, Jeremy
ABSTRACT: The national attention brought to high-profile sex crimes such as the Penn State scandal of 2011 and the Catholic Church scandal of 2002 has elevated public awareness of what can be appropriately referred to as pedophilia. Perceived as a public health threat, pedophilia has become a priority news item for its lascivious and predatory characteristics that instill fear within a widespread audience. This article conveys three ideas essential to pedophilia crisis communication. First, a brief introduction of pedophilia is offered as a social construct and catalyst for moral panic within organizations and their communities. Second, a review of modern and postmodern crisis frameworks is offered to examine an organizational approach to pedophilia and its Foucauldian conception as a rupturing, discursive formation. Third, a call for organizations to embrace ruptures in their pedophilia crisis response is advanced to align their activities with the prevailing historical moment rather than within metaphysical traditions.